2010
DOI: 10.1371/journal.pntd.0000596
|View full text |Cite
|
Sign up to set email alerts
|

An “In-Depth” Description of the Small Non-coding RNA Population of Schistosoma japonicum Schistosomulum

Abstract: Parasitic flatworms of the genus Schistosoma are the causative agents of schistosomiasis, which afflicts more than 200 million people yearly in tropical regions of South America, Asia and Africa. A promising approach to the control of this and many other diseases involves the application of our understanding of small non-coding RNA function to the design of safe and effective means of treatment. In a previous study, we identified five conserved miRNAs from the adult stage of Schistosoma japonicum. Here, we app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 63 publications
1
72
1
Order By: Relevance
“…In flatworms, miR-61 has been reported in S. mediterranea [14] and Sc. japonicum [26]. We also found that E. multilocularis and E. granulosus harbored one miR-61 gene locus and the pre-miRNAs of miR-61 had canonical secondary structures ( Fig.…”
Section: Identification Of Known Mirnas In H Microstomasupporting
confidence: 55%
See 1 more Smart Citation
“…In flatworms, miR-61 has been reported in S. mediterranea [14] and Sc. japonicum [26]. We also found that E. multilocularis and E. granulosus harbored one miR-61 gene locus and the pre-miRNAs of miR-61 had canonical secondary structures ( Fig.…”
Section: Identification Of Known Mirnas In H Microstomasupporting
confidence: 55%
“…However, we did not determine the genomic locus for miR-8 using corresponding pre-miRNA sequences in platyhelminths (data not shown), expression of which has been confirmed experimentally in S. mediterranea, Sc. japonicum, E. multilocularis and E. granulosus [14,17,26]. This is explained by the heterogeneity of the miR-8 gene.…”
Section: Identification Of Known Mirnas In H Microstomamentioning
confidence: 99%
“…Identification and characterization of a set of parasite-derived miRNAs in both S. mansoni (239,240) and S. japonicum (241)(242)(243)(244) provided the basis for their detection in the circulation. The presence of schistosome-specific miRNAs was first reported for the plasmas of S. japonicum-infected rabbits, by Cheng et al (245) and then by Hoy et al (246), who demonstrated elevations of several parasite-derived S. mansoni miRNAs, including sma-miR-277, sma-miR-3479-3p, and bantam, in a mouse model at 8 weeks postinfection.…”
Section: Detection Of Circulating Mirnasmentioning
confidence: 99%
“…In S. japonicum, it had been well established for a while that the usages of siRNAs were able to artificially induce specific endogenous mRNA degradation at transcript level (Cheng et al 2005b;Cheng et al 2009). Very recently, a considerable number of miRNAs have also been identified in different development stages of schistosomes and further studies indicated that the expression profiles of these miRNAs were associated with parasite development, suggesting that miRNAs could be involved in regulating schistosome development Hao et al 2010;Wang et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Schistosomes have a complex life cycle associated with dramatic morphological transformations and rapid physiological adaptations, suggesting that miRNAs/siRNAs could play crucial roles in schistosome development (Cheng et al 2005b;Cheng et al 2009;Huang et al 2009;Hao et al 2010;Wang et al 2010). However, it still remains unknown how many Argonaute proteins are present in S. japonicum and whether their expression profiles are associated with parasite development.…”
Section: Introductionmentioning
confidence: 99%